Nano‐Kirigami Structures and Branched Nanowires Fabricated by Focused Ion Beam‐Induced Milling, Bending, and Deposition. Issue 28 (17th July 2022) - Xia, Deying; Notte, John
Abstract: 3D nanostructures hold the key to building custom devices with special and flexible functionalities. Ion beam‐induced bending and folding are used for the fabrication of 3D nanostructures from prepared 2D nano‐patterned membranes. Tensile and compressive stresses can be introduced within the layers of a thin membrane under ion beam irradiation to manipulate and control the formation of nano‐kirigamis. Both localized and broader ion beam irradiation can be used to induce bending in the membrane with remarkable control of the bending angle and direction. In this work, an approach to fabricate nano‐kirigamis with focused ion beams (FIBs) is developed. First, helium or neon ion beams are used to mill 2D patterns into the planar membrane with good accuracy, nanoscale, and less damage. Subsequently, gallium ion beam is used to broadly and uniformly irradiate the patterned region to induce out‐of‐plane bending to form nano‐kirigamis. Both upward and downward bending are observed for different thicknesses of membranes. The bending angle is easily controlled by varying the irradiation dosage. Moreover, with FIB‐induced deposition, nanopillars, or nanowires (NWs) can be grown on the membrane before or after bending. Various complex 3D nanostructures and branched NWs can be fabricated using this approach. Abstract : Both upward‐bending and downward‐bending nano‐kirigami structures with well‐defined dimensions in nanoscale and controllable bending degree are fabricated with light ion beam milling and broadly heavy‐ion beam irradiation. Tilted, bent and branched nanowires (NWs) are also easy to fabricate on these bending structures using ion beam‐induced deposition, local ion irradiation on NWs, and two‐step deposition methods.